Pengaruh Komunikasi dan Kerja Sama Tim terhadap Kinerja Pegawai PT Perkebunan Nusantara II Kebun Patumbak - Ramadhana, Ilham; Iriani, Iriani; Husin, Ahmad (Universitas Islam Islam Sumatera Utara, 2024)
The formulation of the problem in this study is whether communication and teamwork have an effect on the performance of employees of PT Perkebunan Nusantara II Kebun Patumbak. The purpose of this study is to determine the effect of communication and teamwork on the performance of employees of PT Perkebunan Nusantara II Kebun Patumbak. The population in this study was 34 people, and the sample was 34 employees. The approach to this research is a quantitative approach. Data collection techniques were carried out through questionnaires to respondents, and interviews. The testing method used SPSS.20. Data analysis in this study used validity tests, reliability tests and multiple linear regression analysis. The classical assumption test in this study used normality tests, multicollinearity tests, and heteroscedasticity tests. The hypothesis in this study used partial tests (t-tests), simultaneous tests (f-tests) and determination tests (R2). Based on the results of the study, it can be concluded that Communication has a positive and significant influence on employee performance, namely the t-count value t-table (3.261 1.693) with a significance level of 0.003 0.05. Teamwork has a positive and significant influence on employee performance, namely the t-count value t-table (2.446 1.693) with a significance level of 0.020 0.05. And Communication and Teamwork simultaneously have a positive and significant influence on employee performance, namely the F-count value F-table (47.1363.30) with a significance level of 0.0000.05. And the result of the determination coefficient R2 is 0.753. This shows that in terms of employee performance at PT. Perkebunan Nusantara II, Kebun Partumbak is influenced by Communication and Teamwork as much as 75.30% while 24.70%. The rest is influenced by various other factors that are not used as objects in this study